The World Bank’s Role in and Use of the Low-Income Country Debt Sustainability Framework : Approach Paper - Independent Evaluation Group (Washington, DC : World Bank, 2022)
Interest is high on the World Bank’s role in and use of the Low-Income Country Debt Sustainability Framework (LIC-DSF) in light of the sharp rise in debt stress among low-income countries and a changing global risk landscape in the years leading up to and resulting from the coronavirus pandemic (COVID-19). Since 2015, the number of IDA-eligible countries at high risk of or in debt distress has more than doubled. As the key instrument to assess the debt sustainability of IDA eligible countries, the LIC-DSF is intended to guide the World Bank’s advice and support to these countries. This evaluation seeks to assess how the World Bank contributes to the LIC-DSF, how it uses LIC-DSF output in various corporate and country-level decisions, and how it can better leverage the LIC-DSF to address debt vulnerabilities in LICs. In doing so, it will seek to identify opportunities for the World Bank to strengthen its role in the preparation and use of the LIC-DSF in a changing global context and to highlight potentially important questions that may need to be addressed in the upcoming joint review, including the extent to which the LIC-DSF meets IDA’s needs in serving its clients. Recommendations from this evaluation will focus on aspects of the LIC-DSF that are within the World Bank’s ability to change or influence.